ANALISIS KINERJA KARYAWAN BANK PANIN KCU KOTA SURAKARTA - Windy Helena; Sudarwati Sudarwati; Istiqomah Istiqomah (ITB AAS INDONESIA Surakarta, 2020)
This study aims to determine whether there is an influence of organizational culture, work stress, and work rotation on employee performance. The population in this study were all employees of Bank Panin KCU Surakarta. The sampling technique uses purposive sampling method. Based on the purposive sampling method, a sample of 78 employees was obtained. Data analysis method used in this study is to use multiple linear regression analysis. Based on the results of simultaneous testing (F test) shows that the independent variables (organizational culture, work stress, and job rotation) have a positive and significant effect on the dependent variable (employee performance). Based on partial testing (t test) shows that organizational culture variables, work stress, and job rotation have a positive and significant effect on employee performance. Based on the coefficient of determination test (R2) obtained 78.2%, these results indicate that the dependent variable (employee performance) can be explained by the independent variables (organizational culture, work stress, and job rotation), while the remaining 21.8% is influenced by variables in outside this research. Keywords: Organizational Culture, Job Stress, Work Rotation, Employee Performance